1992
DOI: 10.3109/00952999209001608
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Use and Withdrawal: The Effect on Sleep and Mood

Abstract: Three recreational cocaine users (age, 26.7 years), after one adaptation night, spent 5 days and nights in the laboratory where their EEG, EOG, and submental EMG were recorded during all of their sleep. On the second afternoon and evening of the study, subjects used an estimated 1 to 2 g cocaine intranasally. They all slept between 2:00 A.M. and 9:00 A.M. that night. Blood samples were drawn each evening and morning. Absolute plasma cocaine levels and patterns of elimination were consistent with subjects repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 5 publications
2
50
2
1
Order By: Relevance
“…Thus, the modulation of alpha frequency appears to be affected throughout the withdrawal period. In this respect, it is interesting that the phenomenon of electrophysiological rebound in cocaine withdrawal has been reported by Watson et al [8], in a study of sleep in 3 recreational cocaine users. Rebound of REM sleep, percentage, density and latency were reported after 2 days of abstinence.…”
Section: -Min Recording Period the Authors Suggested That This Incmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the modulation of alpha frequency appears to be affected throughout the withdrawal period. In this respect, it is interesting that the phenomenon of electrophysiological rebound in cocaine withdrawal has been reported by Watson et al [8], in a study of sleep in 3 recreational cocaine users. Rebound of REM sleep, percentage, density and latency were reported after 2 days of abstinence.…”
Section: -Min Recording Period the Authors Suggested That This Incmentioning
confidence: 97%
“…The results of this investigation are consistent with this view, in that injec tors exhibited more power in the beta band on day 2 than did smokers, and a greater change from day 2 to day 6 than did smokers. The relationship between these EEG changes and the greater cognitive impairment reported for intravenous users compared to smokers [8] is currently under investigation.…”
Section: -Min Recording Period the Authors Suggested That This Incmentioning
confidence: 99%
“…Psychological symptoms that occur after chronic use include somatic problems (Johanson et al 1999;Watson et al 1992), eating disorders (Ross-Durow and Boyd 2000), anxiety and depression (Beckwith et al 1999;Falck et al 2002). Associations between chronic cocaine use and conditions such as obsessive-compulsive disorder (Crum and James 1993), paranoia (Espinosa et al 2001;Lejoyeux et al 2000), schizophrenia (Bowers et al 2001), and antisocial personality disorder (Falck et al 2004;Ladd and Nancy 2003) have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…rug addiction is associated with disruptions in sleep and circadian rhythmicity (1)(2)(3). Moreover, in animal models of addiction, several reward-related behaviors exhibit clear circadian regulation.…”
mentioning
confidence: 99%